The religions of Tibet - Hoffmann, Helmut, 1912-1992 (Routledge library editions. Tibet, 2019)
This book, first published in 1961, examines the old Tibetan Bon religion, the development of Buddhism in India and Tibet, and covers the religious struggles of the eighth and ninth centuries. It also describes the rise of the Lamaist sects and the priest state of the Dalai Lamas, and taken as a whole is a study of the development of the character of Tibet itself.